Portal Annular Pancreas – A Case Report - G, Padmavathi; KL, Varalakshmi; N Nayak, Jyothi (International Journal of Medical Research and Review, 2014)
Portal annular pancreas is one of the rarest congenital anomaly of the pancreas. This variation was noted in a formalin fixed male cadaver aged about 60yrs during the course of routine anatomy dissection in MVJ Medical college and research hospital.Here the pancreatic parenchyma not only enclosed the second part of duodenum but also had surrounded the portal vein (PV). Such a variation requires careful consideration by the surgeon and gastroenterologists while performing pancreatic resection and various other procedures pertaining to the pancreas and duodenum.